TECHNOLOGICAL APPLICATIONS IN THE TEACHING AND LEARNING PROCESSES OF BUSINESS EDUCATION IN SECONDARY SCHOOL - Flores, Alejandra Aguero (2022)
This article aims to guide and encourage teachers to use technological applications, for the development of content adapted to the educational context in which they work, although there are resource limitations in the different educational centers, it should not be left aside, since, These tools promote student skills, competencies, interest, criticality, and motivation through the integration of gamification, collaborative activities, infographics, presentations, quizzes, exams, videos, and comics that recreate a class that breaks with the traditional model. The Commercial Education teacher, who works in the different modalities offered by the secondary education system at the national level, agrees with the need for technological updating, referring to the teaching and learning process that has evolved the way in which classes were taught.